The Interplay Between Ozone and Urban Vegetation—BVOC Emissions, Ozone Deposition, and Tree Ecophysiology - Fitzky, Anne Charlott; Sandén, Hans; Karl, Thomas; Fares, Silvano; Calfapietra, Carlo; Grote, Rüdiger; Saunier, Amélie; Rewald, Boris (Frontiers in Forests and Global Change, 2019)
Tropospheric ozone (O3) is one of the most prominent air pollution problems in Europe and other countries worldwide. Human health is affected by O3 via the respiratory as well the cardiovascular systems. Even though trees are present in relatively low numbers in urban areas, they can be a dominant factor in the regulation urban O3 concentrations. Trees affect the O3 concentration via emission of biogenic volatile organic compounds (BVOC), which can act as a precursor of O3, and by O3 deposition on leaves. The role of urban trees with regard to O3 will gain further importance as NOx concentrations continue declining and climate warming is progressing—rendering especially the urban ozone chemistry more sensitive to BVOC emissions. However, the role of urban vegetation on the local regulation of tropospheric O3 concentrations is complex and largely influenced by species-specific emission rates of BVOCs and O3 deposition rates, both highly modified by tree physiological status. In this review, we shed light on processes related to trees that affect tropospheric ozone concentrations in metropolitan areas from rural settings to urban centers, and discuss their importance under present and future conditions. After a brief overview on the mechanisms regulating O3 concentrations in urban settings, we focus on effects of tree identity and tree physiological status, as affected by multiple stressors, influencing both BVOC emission and O3 deposition rates. In addition, we highlight differences along the rural-urban gradient affecting tropospheric O3 concentrations and current knowledge gaps with the potential to improve future models on tropospheric O3 formation in metropolitan areas.